2008
DOI: 10.1159/000116885
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-Alpha Agonist Fenofibrate Induces Renal CYP Enzymes and Reduces Blood Pressure and Glomerular Hypertrophy in Zucker Diabetic Fatty Rats

Abstract: We have previously shown that fenofibrate, a peroxisome proliferator-activated receptor-α activator, increases renal cytochrome P450 (CYP)-derived eicosanoids and improves endothelial function in pre-diabetic obese rats. The present study was designed to explore the efficacy of fenofibrate on blood pressure and renal injury in the advanced stage of type-2 diabetes. 26-week-old male Zucker diabetic fatty rats (ZDF) were fed fenofibrate (100 mg/kg/day) for 6 weeks. Chronic treatment with fenofibrate normalized s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 79 publications
3
38
1
Order By: Relevance
“…It has been recently reported that inhibition of cyclin D1 in MCL cells Effects of fenofibrate on mantle cell lymphoma Z Zak et al blocks cell proliferation but is not sufficient to induce cell death in these cells. 35 Downregulation of cyclin D1 by PPARa agonist has been described in studies of human smooth muscle cells, 36 kidney cells 37 and cancer cells. 16,38 We decided to investigate whether fenofibrate has an effect on the regulation of cyclin D1.…”
Section: Minomentioning
confidence: 92%
“…It has been recently reported that inhibition of cyclin D1 in MCL cells Effects of fenofibrate on mantle cell lymphoma Z Zak et al blocks cell proliferation but is not sufficient to induce cell death in these cells. 35 Downregulation of cyclin D1 by PPARa agonist has been described in studies of human smooth muscle cells, 36 kidney cells 37 and cancer cells. 16,38 We decided to investigate whether fenofibrate has an effect on the regulation of cyclin D1.…”
Section: Minomentioning
confidence: 92%
“…The presence of hypertension in STZ rats is controversial. In Zucker diabetic-fatty (ZDF) rats, changes in blood pressure were not observed at 7 weeks of age, but increases were observed after 13 weeks of age [13,20]. ZDF rats are considered to show hypertension with aging.…”
mentioning
confidence: 99%
“…16 PPARa is also well known as a determinant of the development of hypertension and renal damage, especially in AT-II-induced hypertensive rats. 21,23,24,30 Induction of the renal expression of CYP4A enzymes in the kidney using fibrate compounds has been reported to lower BP in SHR, stroke-prone SHR and Dahl salt-sensitive rats. 31,32 We found the inverse pattern of PPARa expression in kidneys of WKY-HF rats compared with that in SHR-HF animals.…”
Section: Discussionmentioning
confidence: 99%
“…It does so through NO production, oxidative stress and cytochrome P450-derived eicosanoids in the kidney. 23,24 Therefore, in this study, we investigated the role of fenofibrate on renal lipotoxicity associated with hypertension and renal inflammation using spontaneously hypertensive (SHR) rats fed a high-fat (HF) diet.…”
Section: Introductionmentioning
confidence: 99%